2016
DOI: 10.3892/mmr.2016.5776
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in atrial fibrillation-associated proteins between the left and right atrial appendages from patients with rheumatic mitral valve disease: A comparative proteomic analysis

Abstract: The majority of proteomic studies have focused on identifying atrial fibrillation (AF)-associated proteins in the right atrium (RA), thus potential differences in AF-associated proteins between the RA and left atrium (LA) remain unknown. The aim of the present study was to perform proteomic analysis to compare the potential differences in AF-associated proteins between the right atrial appendage (RAA) and left atrial appendage (LAA) in patients with rheumatic mitral valve disease (RMVD). RAA and LAA tissues we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Table- 7 ), only LA (Supp. Table- 8 ), and RA + LA to evaluate how AFib develops in the molecular stage [ 19 ]. In our study, molecular aspects of transcriptomics give a foresight about the influences of persistent AFib on human atrial tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Table- 7 ), only LA (Supp. Table- 8 ), and RA + LA to evaluate how AFib develops in the molecular stage [ 19 ]. In our study, molecular aspects of transcriptomics give a foresight about the influences of persistent AFib on human atrial tissues.…”
Section: Resultsmentioning
confidence: 99%
“…This compartment specific phenomenon is not surprising given that differential expression of proteins has been reported in normal fetal heart [ 29 ]. In fact, it has been shown that the mRNA expression of BNP is increased in the atrium, but not ventricle, of streptozotocin-induced diabetic pigs [ 30 ]. Thus, it is not surprising that alterations in proteins can differ between chambers in various disease states, not just DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that alterations in proteins can differ between chambers in various disease states, not just DCM. For example, this phenomenon has been observed with atrial fibrillation [ 30 ], during experimental heart failure [ 31 , 32 ], and in children with congenital heart disease [ 33 ]. Alternatively, this compartment differential suggests that CCDC47 protein is upregulated in the atrium earlier, perhaps more rapidly, than in the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to discover plasma biomarkers in MVD (5) and to identify the role of ion channels (6), the molecular mechanism of AF in MVD remains unclear. Recently, proteomics studies were performed to explore the mechanisms of AF (6)(7)(8)(9)(10). These studies identified the differential proteins (DPs) in the right and left atrial appendage of rheumatic MVD patients (6,7,9), or pathways including ketone body (8) or glutathione (10) metabolism and the peroxisome proliferator-activated receptor (PPAR) pathway (9,10), which are related to postoperative AF (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%